2020
DOI: 10.1093/pcp/pcaa039
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-Trait Genome-Wide Association Studies Reveal Loci Associated with Maize Inflorescence and Leaf Architecture

Abstract: Abstract Maize inflorescence is a complex phenotype that involves the physical and developmental interplay of multiple traits. Given the evidence that genes could pleiotropically contribute to several of these traits, we used publicly available maize data to assess the ability of multivariate genome-wide association study (GWAS) approaches to identify pleiotropic quantitative trait loci (pQTL). Our analysis of 23 publicly available inflorescence and leaf-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…In these cases, it may be appropriate to use a combination of dimension-reduction and variable selection methods to select relevant phenotypes or linear combinations of phenotypes. Methods like principal component analysis or factor analysis have been used extensively to cope with high-dimensional traits (Runcie and Mukherjee, 2013;Wang and Stephens, 2018;Carlson et al, 2019;Sakamoto et al, 2019;Yu et al, 2019;Campbell et al, 2020;Rice et al, 2020;Runcie et al, 2020). These approaches can be used to create derived traits that capture (co)variance in the original data, and marker effects can be easily estimated using GWAS or whole-genome regression approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, it may be appropriate to use a combination of dimension-reduction and variable selection methods to select relevant phenotypes or linear combinations of phenotypes. Methods like principal component analysis or factor analysis have been used extensively to cope with high-dimensional traits (Runcie and Mukherjee, 2013;Wang and Stephens, 2018;Carlson et al, 2019;Sakamoto et al, 2019;Yu et al, 2019;Campbell et al, 2020;Rice et al, 2020;Runcie et al, 2020). These approaches can be used to create derived traits that capture (co)variance in the original data, and marker effects can be easily estimated using GWAS or whole-genome regression approaches.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the power of QTL detection, here a combination of univariate GWAS and multivariate GWAS were used. Compared with traditional GWAS or univariate GWAS, multivariate GWAS or multitrait GWAS showed higher statistical power to detect signals for complex or multiple traits, as has also been demonstrated in studies of the genomic region associated with seed fatty acid in oat and inflorescence and leaf architecture in maize (Carlson et al, 2019;Rice et al, 2020). Our results showed that eight SNPs were detected by both methods, and 10 SNPs were detected only by multivariate GWAS, which proved the greater power of this method and indicate that the 10 SNPs may represent pleiotropic quantitative trait loci for θ cri and K Tr .…”
Section: Discussionmentioning
confidence: 89%
“…The gray track beneath the GWAS SNPs defines the MNase HS portion of the genome (tassel and ear combined), which was used to subset the SNP set Since this analysis was performed using the NAM population, we expect that the haplotype blocks will limit our ability to resolve causal SNPs, regardless of subsetting the functional genome. We also tested this approach in a small association panel, the 282 line Goodman-Buckler maize diversity panel [67], using GWAS results for TBN from [68]. For the subset of markers present in tassel MNase HS regions (n = 71,024), new False Discovery Rate (FDR)-adjusted P-values were calculated using the Benjamini and Hochberg [69] procedure.…”
Section: Long Non-coding Rnas Associate With Accessible Chromatin In mentioning
confidence: 99%